CHANGES IN BIOCHEMICAL PARAMETERS AND FIBROSIS PROCESS BEFORE AND AFTER ANTIVIRAL THERAPY WITH EXTRAHEPATIC MANIFESTATIONS OF CHRONIC VIRAL HEPATITIS C (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Global morbidity and mortality fromhepatitis C virus (HCV) infection continue to increase. Its complications, which include cirrhosis of the liver, hepatocellular carcinoma (HCC), and liverсfailure, cause approximately 700,000 deaths each year. Antiviral therapy can completely cure patients with HCV infection. However, since the disease is initially asymptomatic, many infected people are unaware of their condition, and those who are correctly diagnosed often do not have access to treatment.